Who disciplines management in poorly performing companies? - Mayer, C; Franks, J; Renneboog, L (University of Oxford, 2001)
Economic theory points to five parties disciplining management of poorly performing firms: holders of large share blocks, acquirers of new blocks, bidders in takeovers, non-executive directors, and investors during periods of financial distress. This paper reports the first comparative evaluation of the role of these different parties in disciplining management. We find that, in the UK, most parties, including holders of substantial share blocks, exert little disciplining and that some, for example, inside holders of share blocks and boards dominated by non-executive directors, actually impede it. Bidders replace a high proportion of management of companies acquired in takeovers but do not target poorly performing management. In contrast, during periods of financial constraints prompting distressed rights issues and capital restructuring, investors focus control on poorly performing companies. These results stand in contrast to the US, where there is little evidence of a role for new equity issues but non-executive directors and acquirers of share blocks perform a disciplinary function. The different governance outcomes are attributed to differences in minority investor protection in two countries with supposedly similar common law systems.